2003
DOI: 10.1177/03635465030310050301
|View full text |Cite
|
Sign up to set email alerts
|

Reconstruction of the Coracoclavicular Ligaments with Tendon Grafts

Abstract: Use of tendon graft reconstruction may limit the need for postoperative immobilization and lead to an accelerated rehabilitation program.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
236
6
5

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 233 publications
(256 citation statements)
references
References 42 publications
(68 reference statements)
6
236
6
5
Order By: Relevance
“…Extrapolating from their graphical results, between rest to 90°, about 12° of upward rotation at the AC joint was found during coronal plane abduction. These findings compare favorably to our results of 14 Motion of the scapula relative to the thorax must be the result of a mechanical coupling between movements at the SC and AC joints. To analyze this it is necessary to compare component joint motions to overall scapular motion on the thorax, keeping in mind that SC joint kinematics involve clavicular motion relative to the sternum and AC joint kinematics involve scapular motion relative to the clavicle.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Extrapolating from their graphical results, between rest to 90°, about 12° of upward rotation at the AC joint was found during coronal plane abduction. These findings compare favorably to our results of 14 Motion of the scapula relative to the thorax must be the result of a mechanical coupling between movements at the SC and AC joints. To analyze this it is necessary to compare component joint motions to overall scapular motion on the thorax, keeping in mind that SC joint kinematics involve clavicular motion relative to the sternum and AC joint kinematics involve scapular motion relative to the clavicle.…”
Section: Discussionsupporting
confidence: 88%
“…2,5,26 Additional research into the biomechanics of the AC joint has revealed ways to alter surgical techniques to improve patient outcomes. 3,14 To date, few studies have been published on AC joint kinematics in human subjects. 4,11,27 Historically, Inman et al…”
Section: Discussionmentioning
confidence: 99%
“…The trapezoid ligament, by comparison, is directed laterally and attached to the clavicle anterior to the midline [19,20]. Experimental studies have revealed that the two components of the coracoclavicular ligaments have different functions according to the direction and magnitude of the forces applied [6,14]. The trapezoid ligament provides the major support against compressive loads applied along the axis of clavicle and acts as a secondary restraint to superior translation.…”
Section: Discussionmentioning
confidence: 99%
“…There are several versions of the anatomic approach, varying with biological ligament (Semitendinoses, Gracilis, EHL, and even Palmaris longus), point of fixation (single clavicle hole or 2 holes). Lee et al [23,24] compared tendon grafts with suture materials and Weaver Dunn grafts in a cadaveric model. They reported that the graft sutured on to itself with supplemental sutures was the most secure method of fixation.…”
Section: Ligament Reconstructionmentioning
confidence: 99%